Coaching strategies to optimize team functioning in high performance curling - Collins, J.; Durand-Bush, N. (International Sport Coaching Journal, 2016)
The purpose of this study was to investigate coaching strategies to optimize team functioning in the context of high performance curling. Strategies were elicited from 10 male coaches, 12 women`s teams (N = 49 athletes) and seven men`s teams (N = 29 athletes) competing at an elite level. Over 150 strategies were identified as being essential for functioning effectively as a team and they pertained to the following seven components: (a) individual attributes (e.g., create a player contract), (b) team attributes (e.g., determine and adjust game strategy), (c) the foundational process of communication (e.g., script routines for communication), (d) structural team processes (e.g., determine acceptable behaviour/standards), (e) individual regulation processes (e.g., do self-assessments/check-ins), (f) team regulation processes (e.g., discuss leadership behaviours), and (g) the context (e.g., prepare for the opposition). Implications for coaching interventions are provided.